Ácidos orgânicos e fitase em rações para leitões desmamados - Ruffino, Luciana Moura (2013)
This study aimed to evaluate the performance in the pre-initial phase (6.7 kg to 15.0 kg), initial phase (15 kg to 25 kg), and in the total period (6.7 kg to 25 kg) as well as the digestibility and metabolism coefficients in pre-initial phase (6.7 kg to 15.0 kg) and initial phase (15 kg to 25 kg). The experimental design was in randomized complete blocks. ANOVA was performed and means were compared by Tukey test at 10 % confidence. We used 120 animals, four animals per experimental unit and five replications, to assess performance, and 48 piglets, each animal representing an experimental unit with four replications, to evaluate digestibility,. The treatments were as follows: 1 - control with Pd available at 0.4%; 2 - Pd reduced to 0.15%; 3 - Pd reduced to 0.15%, plus 1,000 FYT/kg; 4 - Pd reduced to 0.15%, plus 1,000 FYT/kg and 0.3% butyric acid; 5 - Pd reduced to 0.15%, plus 1,000 FYT/kg and 0.75% benzoic acid; 6 - Pd reduced to 0.15%, plus 1,000 FYT/kg, 0.3% butyric acid, and 0.75% benzoic acid. The variables studied in performance test were as follows: daily weight gain, total weight gain, daily feed intake, total feed intake and feed conversion rate in the pre-initial and initial phases, and the total period. For the assessment of digestibility and metabolization coefficients we used the method of total collection of faeces and urine. The analyzed variables were apparent digestibility coefficients for dry matter, crude protein, ether extract, calcium and phosphorus in the pre-initial and initial phases. We studied the metabolization coefficients of dry matter, crude protein, crude energy, calcium and phosphorus in the pre-initial and initial phases. In the pre-initial and initial phases and in the total period the best performance results were obtained when piglets were fed a diet containing benzoic acid and phytase. In the pre-initial phase, calcium digestibility was higher in piglets that ingested diet with reduced phosphorus and diet with phytase. In the initial phase, the digestibility coefficients of dry matter, crude protein and ether extract were lower for the animals fed diets with phytase, benzoic acid and butyric acid. In both phases there was no difference in the metabolization coefficients of dry matter, crude protein, ether extract, calcium and phosphorus. We concluded that the tested additives improved the performance of piglets from 6.7 kg to 25,0 kg live weight.